Summary of the NOW'98 Phenomenology Working Group - Bilenky, S; Geiser, A; Giunti, C; Mohanty, S; Otwinowski, S; Sarkar, S; Xing, Z (1999)
Summary of the Phenomenology Working Group at the Europhysics Neutrino Oscillation Workshop (NOW'98), 7-9 September 1998, Amsterdam.